Metropol.x 05.1 Odessa. Urban planning in a global context. Documentation BA + MA Seminar WS 2018/2019. - (:unkn) unknown (My University, 2020)
Odessa, with over one million inhabitants, is one of the most prominent cities of the Ukraine. Directly located at the north west coast of the Black Sea it is the main administrative, cultural and trade centre of the Odessa Oblast and has been a multiethnic city since its foundation. Odessa has 18 universities and higher education centres, with an emphasis on science. This booklet presents the outcomes of a research-based seminar, where students observed, mapped, critically evaluated and visualized various layers of the city of Odessa - a modern post-socialist city - in its socio-cultural, political, economic, and environmental context.
Keywords: Stadtentwicklung; Stadtentwicklungsforschung; Stadtgestalt; Innenstadt; Stadtgeschichte; Baugeschichte; Städtebaugeschichte; Stadtquartier; Bestandserfassung; Studienarbeit; Postsozialistische Stadt